Analisis Konten Akun Instagram @explore_kabupaten_simalungun pada Minat Wisatawan ke Kebun Teh Sidamanik - Nurhasna, Lily Siti; Azhar, Anang Anas (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study aims to determine how content published by the Instagram account @explore_kabupaten_simalungun influences tourists' interest in visiting the Sidamanik Tea Garden. This is important because both positive and negative travel experiences can influence the decision to revisit a destination. In today's digital age, social media plays a significant role in shaping tourists' perceptions and decisions, particularly among younger generations who are highly active on platforms like Instagram. This study employs a qualitative approach, using the Agenda Setting theory as a foundation to assess how media can direct public attention. The analysis technique used is content analysis of posts in the form of photos and video reels posted by the account, which are then further analyzed using the insights feature to determine user interaction levels such as views, comments, and content shares. The results of the study show that visually appealing content, combined with informative and persuasive captions, can shape positive perceptions of Sidamanik Tea Garden among tourists. This contributes to encouraging the intention to revisit, and even to spread information organically through other users. Insight data revealed that the majority of the audience belonged to the younger age group (18–24 years old), and most of them were not regular followers of the account, indicating that the content successfully reached a broad new audience. This study concluded that Instagram is an effective digital promotional tool for enhancing the appeal of local tourist destinations.